2010
DOI: 10.1590/s0102-695x2010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive activity of phenylalanine against damage mutagenic prompted by the acute administration of cyclophosphamide in pregnant and non-pregnant mice using the micronucleus test

Abstract: RESUMO: "Atividade quimiopreventiva da fenilalanina contra danos mutagênicos pela administração aguda de ciclofosfamida em ratas grávidas e não grávidas, utilizando o teste do micronúcleo". A presente pesquisa teve por objetivo avaliar a capacidade quimiopreventiva da fenilalanina. Utilizou-se um lote de fêmeas prenhes e não prenhes divididas nos seguintes grupos experimentais: G1, PBS (0,1 mL/kg p.c.); G2, ciclofosfamida (35 mg/kg p.c.-i.p.); G3, fenilalanina (150 mg/kg p.c.-v.o.) e G4, fenilalanina (300 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Although there are significant differences in the frequency of micronuclei between the negative control group and the groups treated with IR-01, Vaz et al (2016) describes that this isolated fact does not necessarily imply in toxicogenetic damage. Also, according to the results observed in other experiments from our research group ( Oliveira et al , 2009a , 2013 ; Mauro et al. , 2010 ; Pesarini et al , 2014 ; Navarro et al , 2015 ), the baseline frequency of micronuclei can be greater than the frequency observed for the animals treated with IR-01 in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Although there are significant differences in the frequency of micronuclei between the negative control group and the groups treated with IR-01, Vaz et al (2016) describes that this isolated fact does not necessarily imply in toxicogenetic damage. Also, according to the results observed in other experiments from our research group ( Oliveira et al , 2009a , 2013 ; Mauro et al. , 2010 ; Pesarini et al , 2014 ; Navarro et al , 2015 ), the baseline frequency of micronuclei can be greater than the frequency observed for the animals treated with IR-01 in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, the lowest supplementation dose of phenylalanine presented the highest antimutagenic activity and, consequently, reduced damage to a greater extent. There was no dose-response curve for the doses tested (Mauro et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…No reports were found in the literature about the ability of phenylalanine to prevent teratogenesis. There is only one report of phenylalanine chemoprevention related to an alkylating agent, which is also from our group (Mauro et al, 2010). We previously studied 2 groups of female mice, pregnant and not pregnant, treated with the same doses and followed the same procedures used in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding the results for mutagenicity in Preadmet software, all screened and reference molecules were classified as mutagenic. Even showing mutagenicity, where elimination of molecules for this reason would be premature, studies with rats have shown that a mutagenic molecule when administered in combination with an antimutagenic (chemopreventive) agent may cause suppression of the mutagenic action [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%